THE EXISTENCE OF THE SUWAWA LANGUAGE IN THE ENORMITY OF MODERNIZATION AND MULTICULTURALISM (Eksistensi Bahasa Suwawa dalam Dahsyatnya Terjangan Modernisasi dan Multikulturalisme) - Fatmah AR. Umar (SAWERIGADING, 2021)
The Suwawa language (Bonda) is a tiyombu (ancestor) language. However, due to the development of science and technology, the existence of this language began to be recessive and marginalized. This paper aims to describe (1) the existence of the Suwawa people in the view of modernization and multiculturalism, (2) the type of modernization and multiculturalism adopted by the Suwawa people, (3) factors that cause changes in the existence of the use of the Suwawa language, (4) the impact of modernization and multiculturalism on the existence of the use of the Suwawa language, and (5) efforts to maintain the existence of the Suwawa language in the enormity of modernization and multiculturalism. The method employed is qualitative-descriptive with data collection instruments through observing/recording, participative conversation, and taking notes.  The results indicate several points. First, in the view of modernization and multiculturalism, the Suwawa people have been exposed to: (i) modernization, (ii) modernity, and (iii) multiculturalism with specific characteristics. Second, the type of multiculturalism and modernization adopted by the Suwawa people is (i) isolationist, (ii) accommodative, (iii) autonomous, (iv) critical/interactive, and (v) cosmopolitan. Third, factors that cause changes in the existence of the use of the Suwawa language are (i) language power, (2) language attractiveness, and (3) language pressure. Fourth, the impact of modernization and multiculturalism on the existence of the Suwawa language are (i) positive impact dan (ii) negative impact. Fifth, efforts to maintain the Suwawa language's existence in the enormity of modernization and multiculturalism are pursued through empowering (1) families, (2) educators, (3) community organizations, (4) professional organizations, (5) traditional stakeholders, (7) religious leaders, (8) mass media managers, and (9) the government.